Marketing Mix Berbasis Price Discount dan Bonus Packs Untuk Bisnis Online - Alisia Muamanah; Achmad Fawaid (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2019)
In the era of global science and technology development and overall all lines of life, all aspects of life are touched by internet access included in the business world. Marketing of products and services sold online known as e-commerce or e-business is also used by online shop Nala Hijab. The purpose of this study was to determine consumer perceptions of price discount and bonus packs on the attractiveness of purchases and the level of satisfaction felt by customers Nala Hijab. This study uses a qualitative descriptive approach. The result showed that online promotion price discount and bonus packs and the perception of price perceptions of each other had significant effect on the value of customer satisfaction and trust in the Nala Hijab store. The result of this study indicate that the promotion carried out by Nala Hijab is appropriate, because it can influence consumer purchasing decisions through perceived value of satisfaction and trust. The accuracy of the Nala Hijab online store in taking marketing stimulation actions on products, prices, and promotion mix is a success in taking action to maintain business success competitiveness.